Spontaneous Imbibition Test of Low Salinity Injection at Low Saline Waxy Crude Carbonate - Hidayat, Fiki; Erfando, Tomi; Maulana, Borry Frima (Journal of Earth Energy Engineering, 2018)
Low salinity waterflooding (LSW) is categorized as one of emerging EOR technologies. It is done by injecting water with different salt composition and/or concentration. The research has been carried out for both sandstone and carbonate with the results looks promising. However, most of this research still concentrated in the north sea, middle east and North America region. This article discusses the applicability of low salinity waterflooding methodology in Indonesia. Spontaneous imbibition test is carried out to observe the recovery gain from a various combination of concentration and composition of the injected brine. The change of pH of the brine is also examined in order to confirm the pH effect mechanism. Three different concentration of brine (500 ppm, 5.000 ppm, and 10.000 ppm), three different brine composition (NaCl, CaCl2, and MgCl2) and high paraffinic crude oil are used as the fluid sample. It is found that the increased oil recovery is significant at a salinity of 10,000 ppm for MgCl2 and 5,000 ppm for NaCl ions. While the lowest recovery was shown by the test at a salinity of 500 ppm